Fees and expenses schedule 2010 - 6682 Royal Institute of British Architects (London : RIBA Publishing, 2012)
This schedule is for detailing the fees and expenses for the project and may be used with any of the RIBA Agreements 2010, 2012 revision. Where used with the Standard Agreement, it is an essential component if the Memorandum of Agreement is used to execute the contract. However, it is merely optional if used in conjuction with any of the Model Letters, which already allow you detail the fees and expenses for the project. All parties must rely exclusively upon their own skill and judgement or upon their advisers when using electronic components from the suite of RIBA Agreements 2010, 2012 revision, and RIBA and RIBA Enterprises Ltd do not assume any liability to any user or any third party.